Effect of Radioactivity of Technetium-99m on the Autosterilization Process of non-sterile Tetrofosmin Kits - Widyastuti Widyastuti; Enny Lestari; Darma Sangaji (The Journal of Pure and Applied Chemistry Research, 2017)
Technetium-99m labeled radiopharmaceutical is commonly used in nuclear medicines as a diagnostic agent, by mixing the sterile kit with Tc-99m. Manufacturing of kits requires an aseptic facility which need to be well designed and maintained according to cGMP, since mostly kits can not be terminally sterilized. Radiopharmaceuticals as pharmaceuticals  containing radionuclide is assumed to have an autosterilization property, but correlation between radioactivity and capability of killing microorganisms has to be studied so far.  The aim of this study is to investigate the effect of radioactivity on the autosterilization process of radiopharmaceuticals.  The study was carried out by adding Tc-99m of various radioactivity into non-sterile tetrofosmin kits, then the samples were tested for sterility. Sterile tetrofosmin kit and non-sterile kit with no Tc-99m added will be used as a negative control and positive control respectively. The sterility was tested using standard direct inoculation method, by inoculating samples in culture media for both bacteria and fungi and observing qualitatively within 14 days. The results showed that the samples with radioactivity of 1, 3 and 5 mCi changed the clarity of the media to turbid,  conformed with the performance of positive controls but samples with radioactivity of 10 mCi and 20 mCi did not change the clarity of the media, conformed with the performance of negative control, indicating neither growth of bacteria nor fungi.  It is concluded that Tc-99m behaves as an autosterilizing agent at certain radioactivity. Therefore the preparation of Tc-99m radiopharmaceutical can be considered as terminal sterilization rather than aseptic preparation.